Transformational leadership and employee engagement at CHAL hospitals in Lesotho - Doti, Mmello (University of the Witwatersrand, Johannesburg, 2021)
Purpose: This study aimed at improving services at CHAL health facilities and to add to the studies that were conducted previously on the impact of transformational leadership on employee engagement. The impact was investigated through attempting to find relationships between key aspects of transformational leadership, employee engagement and productivity. The aim was to continuously explore ways to enhance profitability and efficient ways of delivering meaningful services for CHAL Health facilities. Research Design, methodology & approach: The study was done from data collected from the employees of two CHAL Hospital. A quantitative study was conducted using the following measures: Cronbach Alpha coefficient for reliability and Correlation Matrix to measure the correlations between variables under transformational leadership and employee engagement domains. Findings and recommendations: The main finding of the study was that transformational leadership has positive relationship with employee engagement. It was also established that employee engagement is a perfect strategy to enhance organisational performance, competitiveness and efficiency. Future recommendation was to acquire leadership skills for all levels of management and establish a goal oriented organisational culture for improving employee engagement
A research report p presented in partial fulfillment for the degree of Master of Business Administration to the Faculty of Commerce, Law, and Management, University of the Witwatersrand, Johannesburg 2021
Keywords: Employee engagement; Employee production; Job satisfication; Leadership; Organizational perfomance; Transformational Leadership; UCTD; SDG-8: Decent work and economic growth